Hysteropexy in the Treatment of Total Uterine Prolapse in a Brazilian Molosser Bitch - Sampaio, Renato Linhares; de Rezende, Rodrigo Supranzetti; Martin, Ian; Rosado, Isabel Rodrigues; Leonel Alves, Endrigo Gabelinni; Antunes de Oliveira, Guilherme Carnevalli; de Oliveira, Arêssa Manúcia (Acta Scientiae Veterinariae, 2019)
Background: Uterine prolapse is an obstetric emergency because the exposed tissue can present edema, devitalization or even gangrene, depending on the evolution time and on the severity of circulatory changes. Haemorrhage due to the rupture of ovarian or uterine vessels can evolve rapidly to hypovolemic shock. More rarely, secondary thromboembolism to the uterine strangulation can be developed, complication that can also lead to death. This study reports the case of a Brazilian Molosser bitch treated by reducing total uterine prolapse, complemented with hysteropexy, in order to prevent recurrence and maintain its reproductive ability. Case: A 5-year-old Brazilian Molosser bitch was attended presenting double firm and tubular mass protruding through the vulva. The patient gave birth to five live pups, the last two of which needed to be pulled. Two days after parturition, she had abdominal contraction when a mass protruded from the vagina. A total uterine prolapse was diagnosed, since both uterine horns were found exposed and inverted, with exposition of the endometrium and the areas of placental implantation, together with the body of the uterus. The tissue was apparently edematous and lightly parched, with the presence of strange bodies, but without signals of circulatory complications or lacerations that could turn a possible reduction and maintenance of the uterus unfeasible. Due to interest of the tutor in preserving the reproductive ability, an internal reduction via ventral medial celiotomy and the fixation of the uterus in the lateral abdominal wall (hysteropexy) was chosen in order to diminish the possibility of relapse in future parturition. Discussion: The definitive treatment of the uterine prolapse can be realized through ovariohysterectomy when the exposed uterine tissue is highly compromised or there is vessel rupture or no reproductive purpose for the female. The amputation of everted tissue through the vulva is also an option, but the risk of intracavitary bleeding during tissue resection must be considered when the uterine and ovarian artery and vein escape to the interior of the abdomen without according hemostasis. In cases which there are no complications of the prolapsed tissue and is desired to maintain the reproductive ability of the female, the internal reduction with hysteropexy is recommended. As the etiology of the uterine prolapse is a condition bound to several factors, in between them multiple pregnancies, relaxation of the uterine ligaments and genetic factors, conditions which can be associated to the cause of the prolapse in the mentioned patient, the hysteropexy was preferred as a complementary technique to uterine preservation and prevention of the prolapse relapse in a possible new parturition. In this case, the reduction of prolapse followed by hysteropexy was preferred, because the female dog was apparently well, without signs of complication of the prolapsed tissue and with satisfactory preoperative evaluation. Adding these to the request of the tutor in maintaining the reproductive ability of the female, since the procedure would not pose as a life risk to it. The absence of severe lacerations and circulatory complications in the prolapsed uterus of the bitch under study and the non-detection of toxemia and septicemia corroborated to the reduction and preservation of the uterus. Even though the uterine prolapse is a rare disease, it is necessary to improve surgical techniques that enable the conservation of the female dog in reproduction. In situations of viability of the prolapsed tissue, the technique of hysteropexy in abdominal wall showed itself effective, concluding that hysteropexy is feasible and efficient as a complementary procedure to the reduction of uterine prolapse, having contributed to avoid relapse and maintaining the reproductive of the subject related in this article.